COVID-19 and conservation: Crisis response strategies that benefit people and nature - Ina Lehmann; Jean Carlo Rodríguez de Francisco; Anna Spenceley (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
The COVID-19 pandemic is a global human health crisis that is deeply intertwined with the global biodiversity crisis. It originated when a zoonotic virus spilled over from wild animals to humans. Viruses can spread easily in disturbed ecosystems, and with increasing contact between humans and wildlife the risk of contagion grows. Conservation is crucial to reduce the risks of future pandemics, but the current pandemic also impacts on conservation in many ways. In this Briefing Paper we suggest strategies to alleviate the pandemic's adverse effects on conservation in the Global South. Many zoonoses originate there, and livelihoods are strongly dependent on natural resources. The paper considers the pandemic's overarching economic implica-tions for protected and other conserved areas, and specific ramifications for the tourism and wildlife trade sectors, which are closely related to these areas. As economies shrink, natural resources come under pressure from various sides. Financial resources are reallocated from the conservation to the health sector, countries decrease environmental protection standards to boost economic recovery, and poor people in rural regions resort to protected wild resources as a subsistence strategy. Together, these trends speed up the loss of biodiversity and ecosystem services and create supportive conditions for the emergence of zoonotic disease and the undermining of livelihoods. Before the COVID-19 pandemic, nature-based tourism was a multi-billion dollar industry, and the temporary breakdown in tourism is having both positive and negative impacts on sustainable development. On the negative side, many people employed in tourism have lost their jobs and livelihoods, and a key source of funding for management of protected areas has been depleted. On the positive side, a temporary decline in tourism has given nature time to recover, and a drop in international flights has lowered global carbon emissions from air travel. The need for the industry to plan its post-COVID outlook offers a chance to promote more community-driven tourism to support inclusion of local people. Wildlife trade - a major spreader of zoonotic viruses - has been banned in response to the pandemic in some countries. Yet social safeguards for local communities dependent on protein from wild animals are still largely missing. Our recommendations to address these challenges are that conservation must remain high on the international agenda, especially in the midst of a global health crisis that could quickly repeat itself if ecosystem destruction continues at the current pace. Environmental legislation must be upheld and funding made available for sustainable livelihoods. The resurgence of nature-based tourism should be supported because of its potential to generate conservation funding and income for local communities. In the meantime, the tourism industry should work on further reducing its environmental footprint and improving community self-determination. Bans on wildlife trade need to be designed in ways that do not undermine communities' need for sources of protein.
Keywords: 330